2021
DOI: 10.1007/s40122-021-00277-6
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Gender on Intravenous Nalbuphine Actions After Major Abdominal Surgery: A Multicenter Study

Abstract: Introduction: Nalbuphine, a synthetic kappaopioid receptor (KOR) agonist and a partial lopioid receptor (MOR) antagonist, has been used for years as an effective analgesic. It has been shown to have a better safety profile than morphine. Considering the long history of use of this drug, it is interesting that only a limited amount of information exists on how gender

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In a randomized double-blind comparative trial including 64 male and 63 female patients undergoing major abdominal surgery, Ayad et al [ 1 ] evaluated the influences of gender on postoperative analgesic efficacy of continuous intravenous nalbuphine with two different dosages. They showed that females were more sensitive than males to the analgesic effects of nalbuphine.…”
Section: Key Summary Pointsmentioning
confidence: 99%
“…In a randomized double-blind comparative trial including 64 male and 63 female patients undergoing major abdominal surgery, Ayad et al [ 1 ] evaluated the influences of gender on postoperative analgesic efficacy of continuous intravenous nalbuphine with two different dosages. They showed that females were more sensitive than males to the analgesic effects of nalbuphine.…”
Section: Key Summary Pointsmentioning
confidence: 99%
“…Finally, regarding the fourth comment, which related to adverse events (AEs), the AEs associated with nalbuphine are slightly different from those associated with other l-opioid receptor (MOR) agonists, as nalbuphine is a j-receptor agonist and a partial MOR antagonist. The AEs registered in the study of Ayad et al [1] reflect this difference, with more sedation, nausea, and vomiting events but much less respiratory depression and pruritus observed [8]. Although this study was not sufficiently powered to quantitatively assess any single type of AE, there was a significant higher incidence of AEsmostly sedation, nausea, and vomiting-in females, as reported in Table 3 of Ayad et al [1], which is in agreement with the side effects most commonly encountered with nalbuphine use [8].…”
mentioning
confidence: 99%
“…The AEs registered in the study of Ayad et al [1] reflect this difference, with more sedation, nausea, and vomiting events but much less respiratory depression and pruritus observed [8]. Although this study was not sufficiently powered to quantitatively assess any single type of AE, there was a significant higher incidence of AEsmostly sedation, nausea, and vomiting-in females, as reported in Table 3 of Ayad et al [1], which is in agreement with the side effects most commonly encountered with nalbuphine use [8]. In our study, this gender difference was clinically noticed for a dose of 2 mg/h and both clinically and statistically noticed for a dose of 1 mg/h.…”
mentioning
confidence: 99%
See 2 more Smart Citations